Molecular Taxonomy and Characterization of Thermotolerant Komagataeibacter Species for Bacterial Nanocellulose Production at High Temperatures - Kallayanee Naloka (Science Faculty of Chiang Mai University, 2019)
Nineteen isolates (MSKU 1-MSKU 19) were selected from 166 isolates of acetic acid bacteria (AAB) which in turn were isolated from 47 rotten fruit samples in Thailand. These isolates were identified as Komagataeibacter based on 16S rRNA gene and 16S-23S rRNA gene ITS sequences. All 19 isolates are thermotolerant bacterial nanocellulose (BNC) producers that can grow up to 37 ºC. Among the 19 isolates, MSKU 12 was the most effective BNC producer at high temperatures. It exhibited the highest amount of BNC, 11.11 ± 1.50 µmol sugar per mg of protein (measured as sugar content), which was 7.8 fold higher than that of the amount produced by K. oboediens JCM 16937T in YPGD-1A2E medium at 37 ºC. In addition, MSKU 12 produced the highest amount of BNC of 7.6 ± 1.01 g/L dry weight in HS-1A2E medium at 30 ºC. This was at least 1.5 fold higher than that of other Komagataeibacter strains. Interestingly, this isolate also produced BNC of 2.2 ± 0.03 g/L dry weight in HS-1A2E medium at 37 ºC, which is impossible for the related type strain, K. xylinus BCC 49175T. MSKU 12 possessed a stable BNC-producing activity due to the absence of the insertion sequence elements, the IS1031 family, which were detected in the genome of its related type strain and the other type strains of Komagataeibacter. These findings indicate that Komagataeibacter sp. MSKU 12 is a potentially effective BNC producer at high temperatures.